Faktor-faktor yang memengaruhi ketidakminatan siswa terhadap matematika - Firmansyah, Ahmad Maulana (Maliki Interdisciplinary Journal, 2024)
The purpose of this research is to identify the elements that influence students disinterest in mathematics subjects. This research uses the SLR (Systematic Literature Review) method, which provides a systematic and transparent means for collecting, synthesizing, and assessing study findings on a topic or question. Secondary data sources for this research include J-Pmat, Repository, Researchgate, and APA PsycNet. Research stages include data collection, data analysis, and concluding. In the process of concluding, the author reviews and identifies journals systematically, each process is based on predetermined steps. Next, extracting all found articles was performed. Studies show that two factors influence students' disinterest in mathematics, namely internal factors and external factors. Internal factors that contain psycho-physical disorders or deficiencies and originate from oneself. On the other hand, external factors are influenced by the circumstances and conditions in the surrounding environment that support education. These three environments are divided into the school environment, family environment and community environment.